Impact of Collaborative Culture as a Mediator for Performance Management System on Employees’ Motivation in Construction Sectors of Afghanistan - Naqibullah Shaikhzada; Safiullah Shinwari; Dr. Bilal Khan (Indus Journal of Social Sciences, 2025)
This study investigates the impact of performance management systems (PMS) as a mediator for employees’ motivation on collaborative culture within the construction sector of Kabul, Afghanistan. Utilizing a survey-based approach, data was collected from employees across various construction firms to assess the relationships between these variables. The analysis was conducted using regression analysis through the Process Hayse Macro, which allowed for the examination of mediation effects. The findings reveal a significant relationship between employees’ motivation and collaborative culture, with the performance management system playing a crucial mediating role. Specifically, the study highlights that an effective PMS enhances employees’ motivation, which in turn fosters a more collaborative work environment.